Islamic Ethnomethodology Studies to Uncover Local Cultural Values Behind Capital Accounting Practices - Mohamad Anwar Thalib; Lizatul Zanna; Fatma Rauf; Susanti Rasyid (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Purpose: The purpose of this study is to find the value of local wisdom behind the business capital of food stalls in Gorontalo. Methodology : the type of method used is qualitative. there are five stages of data analysis namely charity, knowledge of faith, revelation information, and courtesy. Findings: The informants obtained capital sourced from debt through their relatives, so there was no guarantee, interest, and flexible terms of debt repayment. Meanwhile, informants who used capital sourced from personal funds were because places to eat, equipment, and business equipment were inherited from their parents. So that informants only need to spend a small amount of money on starting a business. The capital practiced by the owners of the food stalls is conditional on non-material values ​​in the form of kinship. In the culture of the people of Gorontalo, the value of kinship is one of the spirits that the elders often internalize through the expression